Social capital: Cross-industry and cross-state comparison among Malaysian women micro-entrepreneurs - Rajennd Muniady; Abdullah Al- Mamun; P. Yukthamarani Permarupan; Noor Raihani Zainol; Mohd. Rosli Mohamad (MCSER Publishing, 2016)
The objective of this study is to determine the distribution of social capital across industries and states in Peninsular Malaysia, since social capital is considered one of the key factors that contribute to the performance of micro-enterprises. This study employs the cross-sectional approach and quantitative data were collected through structured interviews from 417 women micro-entrepreneurs in Peninsular Malaysia. It was found that the distribution of social capital is the same across industries except for ‘shared meaning and interpretation’ and ‘cognitive social capital’. However, findings reported a significant difference in items of social capital among the states, except for ‘network density’. Policy makers should therefore focus on interactive programs in order to increase the social capital of the states with a low level of social capital as social capital is linked to enterprise performance and economic development.